The clinical assessment and management of child and adolescent obesity - Baur, Louise (Henry Stewart Talks, 2011)
Do obese children/adolescents present to clinical services?, Clinical assessment of the obese child/adolescent (anthropometry, history and examination, investigations), Management of the obese child/adolescent (evidence for lifestyle interventions, elements of behavioural change, pharmacotherapy, severe obesity), Providing a clinical service to obese children/adolescents